Penerapan Algoritma C4.5 untuk Memprediksi Profit Perusahaan di PT JMS Batam - Hakim, Arif Rahman (Riset Sinergi Indonesia (RISINDO), 2025)
The advancement of technology and information has significantly transformed various sectors, especially the business world. With rapid developments, access to fast and accurate data has become easier, eliminating the need for lengthy searches. This evolution has gained the attention of many, particularly companies managing industrial estates, where effective decision-making relies heavily on data analysis for annual business planning. PT JMS Batam, a subsidiary of PT JMS, manages the Tunas industrial area. Established in 2008, it is located at Jl. Raja Isa - Tunas Ruko Industrial Estate Blok 1A No. 10 Batam Center. The company has accumulated a wealth of performance-related data over the years; however, this information has not been effectively utilized. By implementing data mining technology, specifically the C4.5 algorithm, PT JMS Batam aims to process its untapped transaction data. This approach will help uncover valuable insights that can enhance the company's operations. The focus will be on generating predictive knowledge that can aid in forecasting profit achievement, ultimately supporting better strategic planning and decision-making processes within the organization.